2003
DOI: 10.2527/2003.8161529x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, carcass traits, and plasma amino acid concentrations of gilts fed low-protein diets supplemented with amino acids including histidine, isoleucine, and valine

Abstract: Three experiments were conducted to determine the fifth-limiting amino acid for growing pigs in an 11% CP, corn-soybean meal diet. In each experiment, 36 gilts (initial weight 19.5, 21.9, and 21.0 kg, respectively) were penned individually and fed one of six diets in a randomized block design for 35 d. Diets containing 16, 12, and 11% CP were fed in each experiment. All 12 and 11% CP diets were supplemented with lysine, tryptophan, threonine, and methionine to provide the same total concentrations as those in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
67
2
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 12 publications
19
67
2
8
Order By: Relevance
“…In typical European diets, Val will often be the third to fifth limiting AA in diets for piglets (Figueroa et al, 2003;Mavromichalis et al, 1998;Nørgaard and Fernández, 2009). It has been reported that Val may be involved in appetite regulation acting as a signal of a non-dispensable AA deficiency (Gloaguen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In typical European diets, Val will often be the third to fifth limiting AA in diets for piglets (Figueroa et al, 2003;Mavromichalis et al, 1998;Nørgaard and Fernández, 2009). It has been reported that Val may be involved in appetite regulation acting as a signal of a non-dispensable AA deficiency (Gloaguen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…When low-protein diets are formulated to contain crystalline amino acids, it is likely that several amino acids are co-limiting for performance. It is generally assumed that Val is the fifth-limiting amino acids in corn-soyabean meal-based diets in growing pigs (Figueroa et al, 2003). Barea et al (2009b) estimated the Val requirement expressed on a standardized ileal digestible (SID) basis and relative to Lys to be at least 70% using performance as a response criterion.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, reducing dietary CP level from 20.00% to 13.90% resulted in higher plasma concentrations of lysine, methionine and alanine, this response is in agreement with previous reports that the higher protein degradation of pigs occurred in pigs fed low-CP diet, thus increased the plasma concentration of some free AA . On the other hand, the higher plasma concentrations of lysine and methionine may be related to the higher supplementation of industrial lysine and methionine in low-CP diet (Figueroa et al, 2003). The lower plasma concentration of arginine may reflect the lower dietary provision of arginine in pigs fed low-CP diet.…”
mentioning
confidence: 99%